Reverse augmentation technique in hip revision arthroplasty: a new strategy for the management of acetabular reconstruction - Christian Götze; Christian-Dominik Peterlein (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background The principle of acetabular total hip revision (THR) is based on acetabular reconstruction and restoration of the center of rotation. The use of augmentation in high cranial acetabular defects combined with a cementless revision shell was studied sufficiently. This study aimed to report a case with the use of an augment inside a cementless revision shell as a reverse augmentation technique. Methods We describe the case of an 86-year-old female patient with a massive acetabular defect during second revision for total hip arthroplasty (THA). Two problems occurred: (1) a fixed cemented stem with a nonmodular head size of 33 mm and (2) a high acetabular defect with an elevated rotation center. Results With the distraction technique, allograft filling was used to reconstruct the acetabular defect. A cementless revision shell (REDAPT, Smith and Nephew) with a size of 78 mm was used to stabilize the defect. Locking screws placed cranially and distally were used to stabilize the cup for secondary osseointegration. An augment was placed inside the cup to reconstruct the rotation center. A customized polyethylene liner (outer diameter, 54 mm/inner diameter, 33 mm) was positioned below the augment in the revision cup to reconstruct the center of rotation. An 18-month postoperative X-ray analysis showed a stable construct with full secondary osseointegration. Conclusion This is the first report of an augment used for a reverse technique inside a cementless shell to restore the center of rotation with the use of a customized polyethylene liner. This might be a reliable option for reconstruction of the center of rotation in large cementless revision cups in acetabular Paprosky type III defects. This technical note shows the possibility of using an augment as a reverse technique in a cementless revision cup.